Inequalities and Their Measurement - Almas Heshmati (Institute for the Study of Labor (IZA), 2004)
This paper is a review of the recent advances in the measurement of inequality. Inequality can have several dimensions. Economists are mostly concerned with the income and consumption dimensions of inequality. Several inequality indices including the most widely used index of inequality namely the Gini coefficient is discussed. Non-income inequality includes inequality in skills, education, opportunities, happiness, health, wealth, and others. The direct and indirect effects of inequality in non-income factors on earnings and health are discussed. Results from review of the literature suggest relationship between inequality in income and non-income dimensions. This indicates that one should account for the interrelationship between the different dimensions in the measurement and analyses of inequalities.
Keywords: I30; D31; N30; 330; income inequality; inequality indices; income distribution; Disparitätsmass; Einkommensverteilung; Lebensqualität